The question for release subsectors in the financial law - Лукашев, О. А. (Problems of legality, 2013)
The article analyzes the current views of scientists according to the criteria selection sub rights. It is concluded that, in financial and legal subsector may include legal rules that govern the relationship of large groups of public relations concerning the financial activities of the state and are characterized by certain specific and generic selection.